The industrial organization of execution, clearing and settlement in financial markets - Craig Pirrong (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
The execution, clearing, and settlement of financial transactions are all subject to substantial scale and scope economies which make each of these complementary functions a natural monopoly. Integration of trade, execution, and settlement in an exchange improves efficiency by economizing on transactions costs. When scope economies in clearing are more extensive than those in execution, integration is more costly, and efficient organization involves a trade-off of scope economies and transactions costs. A properly organized clearing cooperative can eliminate double marginalization problems and exploit scope economies, but can result in opportunism and underinvestment. Moreover, a clearing cooperative may exercise market power. Vertical integration and tying can foreclose entry, but foreclosure can be efficient because market power rents attract excessive entry. Integration of trading and post-trade services is the modal form of organization in financial markets, which is consistent with the hypothesis that transactional efficiencies explain organizational arrangements in these markets.
urn:nbn:de:hebis:30-62228
Keywords: 330; Wertpapiergeschäft; Verrechnungsverkehr; Finanzintermediär; Industrieökonomik; Finanzmarkt; Organisation; Theorie